Assessment of primary air on corn straw in a fixed bed combustion using Eulerian-Eulerian approach. (15th May 2018) - Meng, Xiaoxiao; Sun, Rui; Ismail, Tamer M.; El-Salam, M. Abd; Zhou, Wei; Zhang, Ruihan; Ren, Xiaohan
Abstract: In this paper, mathematical modelling is conducted on the combustion of corn straw in a one-dimensional bench combustion test rig, and the effects of the primary air flow rate are assessed over a wide range. Due to complex solid combustion mechanisms and inadequate knowledge of the process, the development of such combustion system is limited. Numerical modelling of this combustion system has some advantages over experimental analysis, although the development of a complete model for this type of combustion system remains a challenge. Due to its characteristic properties, modelling of biomass combustion has to overcome many difficulties. One such problem is displaying the process of initiating the combustion in numerical modelling. This study finds that the volatile release and combustion of char increases, thus increasing the amount of primary air up to a critical point, where the starting time of ignition becomes shorter as the primary air flow rate increases. The peak concentration of NO decreases with the increase of primary air, whereas with the increase in the amount of air, there is a reduction in the release of SO2 as well as a reduction in CO emissions in the bed. Highlights: The effect of primary air on the corn combustion process is investigated. Temperature, rates, and gas species are measured and simulated. The simulation results in the bed are accordant with the experimental results. The peak concentration of NO decreases with the increase of primary air. With the increase of primary air flow, the amount of SO2 generated is reduced.